The Vienna FES Interview Protocol - A mixed-methods protocol to elucidate the opinions of various individuals responsible for the provision of FES exercise - Matthew J. Taylor; ﻿﻿﻿﻿Ché Fornusek; Andrew J. Ruys; Manfred Bijak; Adrian E. Bauman (PAGEPress Publications, 2017)
Functional Electrical Stimulation (FES) is the production of electrically elicited muscle contractions to perform a function or task. It has been used as a method to regain lost body functions or support weak body functions, and as such, has been clinically available since the early seventies. Some methods are applied routinely while others have not been translated to the bedside, or are still largely restricted to laboratory use. Progress in this field might be achieved by a strong cooperation of patients, clinicians, therapists and engineers. A better insight into multiple perspectives may help in understanding the shortcomings of current FES technology. This will help direct future research efforts into design of systems and potential application in relevant populations. In addition, these findings can assist with the translation of FES technology into a community context. We outline an interview protocol designed for use at the 12th Vienna International Workshop on Functional Electrical Stimulation where the mentioned experts from the field of FES met.